2014
DOI: 10.1080/13854046.2014.881554
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Turkish Version of the Montreal Cognitive Assessment Scale (MoCA-TR) in Patients With Parkinson’s Disease

Abstract: The study aimed to examine the reliability and validity of the Turkish version of the Montreal Cognitive Assessment Scale (MoCA-TR) as a screening tool for cognitive dysfunction in Parkinson's disease (PD). A total of 50 patients with PD and 50 healthy controls were included. The screening instruments-MoCA-TR followed by the Mini-Mental Status Examination (MMSE-TR) and MoCA-TR retest within 1 month-and detailed neuropsychological testing were administered to the PD patients. MoCA-TR and MMSE-TR were also admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 23 publications
5
42
2
3
Order By: Relevance
“…Specific studies in the Brazilian population showed that the use of the cut-off of scores of 24 or 25 points had the greater accuracy for the identification of MCI, and that the cut-off scores of 21 or 22 was ideal for the identification of dementia 25 . Studies in patients with PD showed similar findings with some small variations 10, 12,26 . As we cited above, some specific characteristics of our sample, especially the lower educational level, may have reduced the accuracy of MoCA in recognizing patients with PDMCI.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Specific studies in the Brazilian population showed that the use of the cut-off of scores of 24 or 25 points had the greater accuracy for the identification of MCI, and that the cut-off scores of 21 or 22 was ideal for the identification of dementia 25 . Studies in patients with PD showed similar findings with some small variations 10, 12,26 . As we cited above, some specific characteristics of our sample, especially the lower educational level, may have reduced the accuracy of MoCA in recognizing patients with PDMCI.…”
Section: Discussionsupporting
confidence: 69%
“…In general, the accuracy was judged to be superior to that found with the application of the MMSE. Although some studies have shown that ACE-R may be useful for detecting MCI, studies in patients with PD found controversial findings 5,8,10,12,26 . Our study showed that in our sample the best cut-off scores for the ACE-R to best discriminate patients with PDD was < 76.…”
Section: Discussionmentioning
confidence: 99%
“…MoCA has been translated and is available (www.mocatest.org) in more than 40 languages other than English. [14][15][16][17][18][19][20][21][22][23][24][25] Its validity as a screening tool for cognitive dysfunction and its superiority over MMSE have been demonstrated, not only in MCI but also in the setting of Alzheimer disease, stroke, vascular dementia, traumatic brain injury, and frontotemporal dementia. [26][27][28][29][30][31] The usefulness of MoCA as a suitable, accurate, and brief test for screening all levels of cognition in PD has also been established.…”
Section: Introductionmentioning
confidence: 99%
“…Defining a single, optimal MoCA cutoff score from the large number of validation studies is further limited by the fact that the majority of studies have been conducted in specific patient populations, such as those with cerebrovascular conditions (e.g., Cumming et al, 2013;Dong et al, 2010Dong et al, , 2012Freitas et al, 2012b;Godefroy et al, 2011;Pendlebury et al, 2012Pendlebury et al, , 2013Webb et al, 2014;Wong, Lam, et al, 2013a) cardiovascular conditions (Hawkins et al, 2014;McLennan et al, 2011), Parkinson's disease (e.g., Chen et al, 2013;Dalrymple-Alford et al, 2010;Gill et al, 2008;Hoops et al, 2009;Kasten et al, 2010;Krishnan et al, 2015;Ozdilek & Kenangil, 2014;Sobreira et al, 2015), HIV (Koski et al, 2011;Milanini et al, 2014;Janssen et al, 2015;Joska et al, 2016;Overton et al, 2013), Traumatic Brain Injury (Wong, Ngai, et al, 2013b), psychiatric conditions (Gierus et al, 2015;Musso et al, 2014), Huntington disease (Bezdicek et al, 2013), and Korsokoff syndrome (Oudman et al, 2014;Wester et al, 2013).…”
mentioning
confidence: 99%